Women affected by breast cancer— follow up recommendations - Poma, Pedro A. (2017)
Breast cancer incidence has increased, while its mortality has decreased; almost nine out of ten women survive five years after the diagnosis. With a clinical history and physical exam, survivors are evaluated for recurrences, new malignancies, and late effects of its treatment. Asymptomatic survivors do not need to be evaluated for recurrences, but education about healthy lifestyles is necessary.